Enhanced influenza vaccination among healthcare personnel prevents cases despite community burden - Medina-Piñón, Isaí; Padilla-Orozco, Magaly; Mendoza-Flores, Lidia; Garza-González, Elvira; Salazar-Montalvo, Raul G; Flores-Treviño, Samantha; Camacho-Ortiz, Adrián (The Journal of Infection in Developing Countries, 2019)
Introduction: Influenza vaccination for healthcare personnel is not obligatory in Mexico, and compliance relies on promotion and persuasion. The objective of this study was to determine the impact of influenza vaccination compliance on the reduction of influenza and influenza-like illness among healthcare personnel throughout two consecutive influenza seasons. Methodology: A retrospective study comparing cases of influenza and influenza-like illness among vaccinated and unvaccinated healthcare personnel registered in a Mexican 500-bed University Hospital surveillance and immunization registry during seasons 2015-16 and 2016-17. Results: Total influenza immunization compliance was 21.3% and 42.7%, respectively. Reduction of the number of influenza-like illness (58 in 2015-16 and 15 in 2016-17; P = 0.0001) and confirmed influenza cases (28 in 2015-16 and 13 in 2016-17; P = 0.036) was evident. During 2016-17, influenza activity in the community was higher than 2015-16 (4800 and 1338 cases, respectively). Conclusions: Increased influenza vaccination compliance among healthcare personnel was associated with reduction of the overall number of influenza and influenza-like illness cases, even in the setting of high activity of the disease in the community through 2016-17 and reported suboptimal vaccine effectiveness during both seasons.